The Discounted Money Value of Human Life Losses Associated With COVID-19 in Mauritius - Musango, Laurent; Nundoochan, Ajoy; Kirigia, Joses Muthuri (Frontiers in Public Health, 2020)
Background: The objective of this study was to estimate the total discounted money value of human life losses (〖TDMVCL〗_MAURITIUS ) associated with COVID-19 in Mauritius. Methods: The human capital approach (HCA) was used to estimate the 〖TDMVCL〗_MAURITIUS of the ten human life losses linked with COVID-19 in Mauritius as of 25 July 2020. The HCA model was estimated with the national life expectancy of 75.51 years and a discount rate of 3%. A sensitivity analysis was performed assuming (a) 5% and 10% discount rates, and (b) the average world life expectancy of 73.2 years, and the world highest life expectancy of 88.17 years. Results: The human lives lost to COVID-19 had an estimated 〖TDMVCL〗_MAURITIUS of Int 3,120,689, and an average of Int312,069 per human life lost. Approximately 74% of the 〖TDMVCL〗_MAURITIUS accrued to persons aged between 20 years and 59 years. Reanalysis of the model with 5% and 10% discount rates, holding national life expectancy constant, reduced the 〖TDMVCL〗_MAURITIUS by 19.0% and 45.5%, respectively. Application of the average world life expectancy at 3% discount rate reduced 〖TDMVCL〗_MAURITIUS by 13%; and use of the world highest life expectancy at 3% discount rate increased 〖TDMVCL〗_MAURITIUS by 50%. Conclusions: The average discounted money value per human life loss associated with COVID-19 is 12-fold the per capita GDP for Mauritius. All measures implemented to prevent widespread community transmission of COVID-19 may have saved the country 837 human lives worth Int258,080,991. This evidence, conjointly with human rights arguments, calls for increased investments to bridge the existing gaps in universal health coverage.